The Reusable Load Cell with Protection Applied for Online Monitoring of Overhead Transmission Lines Based on Fiber Bragg Grating - Guoming Ma; Naiqiang Mao; Yabo Li; Jun Jiang; Hongyang Zhou; Chengrong Li (Sensors, 2016)
Heavy ice coating of high–voltage overhead transmission lines may lead to conductor breakage and tower collapse causing the unexpected interrupt of power supply. The optical load cell applied in ice monitoring systems is immune to electromagnetic interference and has no need of a power supply on site. Therefore, it has become a hot research topic in China and other countries. In this paper, to solve the problem of eccentric load in measurement, we adopt the shearing structure with additional grooves to improve the strain distribution and acquire good repeatability. Then, the fiber Bragg grating (FBG) with a permanent weldable package are mounted onto the front/rear groove of the elastic element by spot welding, the direction deviation of FBGs is 90° from each other to achieve temperature compensation without an extra FBG. After that, protection parts are designed to guarantee high sensitivity for a light load condition and industrial safety under a heavy load up to 65 kN. The results of tension experiments indicate that the sensitivity and resolution of the load cell is 0.1285 pm/N and 7.782 N in the conventional measuring range (0–10 kN). Heavy load tension experiments prove that the protection structure works and the sensitivity and resolution are not changed after several high load (65 kN) cycles. In addition, the experiment shows that the resolution of the sensor is 87.79 N in the large load range, allowing the parameter to be used in heavy icing monitoring.